3D seismic imaging of lower delta-plain beach ridges: lower Brent Group, northern North Sea - Jackson,CAL; Grunhagen,H; Howell,JA; Larsen,AL; Andersson,A; Boen,F; Groth,A (Journal of the Geological Society of London, 2010)
Three-dimensional seismic reflection data are used to image littoral deposits within the lower Brent Group, northern North Sea. Seismic attribute maps within the unit indicate the development of parallel, high-amplitude stripes up to 15 km in length, 50–100 m wide and spaced 150–200 m apart. In map view these features trend NE–SW to ENE–WSW and are arranged into ‘sets' that display subtly different orientations. Well data in regions where these anomalies are well developed indicate pronounced anomaly-perpendicular thickness variations in sand-rich beach-ridge facies within the Etive Formation and coals and mudstones within the overlying Ness Formation. Based on these observations, the high-amplitude anomalies are interpreted as the seismic expression of coal-filled swales, whereas the adjacent zones of low amplitude are interpreted to represent the cores of sand-rich beach ridges. The geometry of beach ridges identified in the Etive Formation compares favourably with sedimentological and geometric data from modern beach ridges. The results of this study have implications for (1) the stratigraphic context and preservation of beach ridges, (2) datum selection when attempting stratigraphic correlations within the Brent Group, and (3) the exploration and production of hydrocarbons from beach ridge-type reservoirs.